1989
DOI: 10.1037/0735-7044.103.5.998
|View full text |Cite
|
Sign up to set email alerts
|

Reappraising the cerebellum: What does the hindbrain contribute to the forebrain?

Abstract: Although the cerebellum has traditionally been regarded as a motor mechanism, recent behavioral evidence indicates that the human cerebellum is involved in a wider range of functions: in learning, in planning, in judging time, in some emotional and cognitive disorders such as autism, and in some normal mental activities such as the cognitive processing of words. This evidence suggests that the traditional view of cerebellar function now needs to be reassessed and enlarged to include nonmotor as well as motor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
179
0
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(194 citation statements)
references
References 63 publications
11
179
0
4
Order By: Relevance
“…These links include not only frontal motor areas, but also language-related areas such as Broca's region (Desmond et al, 2005;Mariën et al, 2001). As highlighted by Murdoch (2010), "this reciprocal connectivity forms a series of segregated neural loops that are hypothesized to facilitate linguistic function in the same way that the cerebellum enhances motor functions (Leiner et al, 1989). "…”
Section: Functional Topography Of the Cerebellummentioning
confidence: 99%
“…These links include not only frontal motor areas, but also language-related areas such as Broca's region (Desmond et al, 2005;Mariën et al, 2001). As highlighted by Murdoch (2010), "this reciprocal connectivity forms a series of segregated neural loops that are hypothesized to facilitate linguistic function in the same way that the cerebellum enhances motor functions (Leiner et al, 1989). "…”
Section: Functional Topography Of the Cerebellummentioning
confidence: 99%
“…However, as Leiner, Leiner & Dow (1989) note, the human cerebellum (in particular, the lateral cerebellar hemispheres and ventrolateral cerebellar dentate nucleus) has evolved enormously, becoming linked not only with the frontal motor areas, but also some areas further forward in the frontal cortex, including Broca's language area. (Leiner et al, 1989; 1991; Leiner, Leiner & Dow, 1993) concluded that the cerebellum is therefore central for the acquisition of 'language dexterity'. In effect, then, they proposed that the cerebellum is critically involved in the automatisation of any skill, whether motor or cognitive.…”
Section: The Cerebellummentioning
confidence: 99%
“…There is an information-processing system relating to movement and cognitive actions, such as planning, reasoning, and emotion (Leiner et al, 1989). The cerebellum, known to be involved only in voluntary and involuntary motor control, also plays a major role in thought itself (Leiner et al, 1986); the resulting information-processing system may be essential for the manipulation of kinesthetic mind.…”
Section: Mind-brain-body Triad In Healthmentioning
confidence: 99%